2020
DOI: 10.1111/myc.13182
|View full text |Cite
|
Sign up to set email alerts
|

Different susceptibility of spores and hyphae of Trichophyton rubrum to methylene blue mediated photodynamic treatment in vitro

Abstract: Trichophyton rubrum (T ruburm) is the most common dermatophyte worldwide. It is responsible for the majority of dermatomycosis, including tinea manus and pedis, tinea cruris, tinea corporis and tinea unguium. 1 With the increases of immunocompromised population and broad-spectrum antibiotics abuse, the incidence of dermatomycosis has also been on the rise in recent years. 2 Although superficial fungal infections are rarely life-threatening, they can cause damage to the skin appearance and normal function, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…Previous studies have demonstrated that methylene blue with light emission diode is effective and safe, with positive response rates of~85% to 100% [44]. The effective action of such therapy has also been shown in the treatment of dermatophytoses [32,33].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies have demonstrated that methylene blue with light emission diode is effective and safe, with positive response rates of~85% to 100% [44]. The effective action of such therapy has also been shown in the treatment of dermatophytoses [32,33].…”
Section: Discussionmentioning
confidence: 98%
“…Guffey et al [32] found that methylene blue at concentration equal to 0.64 μg/mL (in the original work the concentration defined as 2 μmol/L), the T. rubrum were completely killed by 625 nm red light at the dose of 60 J/cm 2 . Furthermore, Li et al [33] revealed that methylene blue at concentration equal to 0.625 μg/mL and with 20 J/cm 2 energy of 635 nm light showed significant inhibitory effect toward T. rubrum cells. These results are approximately consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations